A review of key technologies for the future of the 2030 network——Beyond 5G - Ziyu XIAO (Dianxin kexue)
ITU-T SG13 established a Focus Group of Network 2030 in 2018 for a two-year study period.FG NET-2030 focuses on the network requirements,scenarios and the network capabilities of the future network,and proposes the key technologies and study directions of the next study period in SG13.Focus on key technology development directions that the industry pays more attention,the network requirements and key technologies of the ITU-T Future Network Architecture Working Group for Beyond 5G and Network 2030 was tracked.The network requirements and challenges for 2030 was summarized,and the key technologies and evolution trends of deterministic networks,new IP architectures,the network-based machine learning architectures and a use case of machine learning applications in 5G network were analyzed.